Rapid Current Account Adjustments : Are Microstates Different? - Imam, Patrick (Washington, D.C. : International Monetary Fund, 2008)
We describe unique aspects of microstates-they are less diversified, suffer from lumpiness of investment, they are geographically at the periphery and prone to natural disasters, and have less access to capital markets-that may make the current account more vulnerable, penalizing exports and making imports dearer. After reviewing the "old" and "new" view on current account deficits, we attempt to identify policies to help reduce the current account. Probit regressions suggest that microstates are more likely to have large current account adjustments if (i) they are already running large current account deficits; (ii) they run budget surpluses; (iii) the terms of trade improve; (iv) they are less open; and (v) GDP growth declines. Monetary policy, financial development, per capita GDP, and the de jure exchange rate classification matter less. However, changes in the real effective exchange rate do not help drive reductions in the current account deficit in microstates. We explore reasons for this and provide policy implications.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet